Strategic pricing of financial options - Volker Bieta; Udo Broll; Hellmuth Milde; Wilfried Siebel (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2009)
The mainstream model of option pricing is based on an exogenously given process of price movements. The implication of this assumption is that price movements are not affected by actions of market participants. However, if we assume that there are indeed impacts on the price movements it no longer possible to apply the standard pricing models. As a result we need an approach explaining interdependent actions. Game theory is in a position to offer proper olutions. This paper applies game theoretic concepts to determine option prices. Consequently, both the option price and the underlyings expiration price are endogenously determined.
Keywords: G13; C72; 330; game theory; Nash equilibrium; option pricing; real option; Optionspreistheorie; Spieltheorie; Nash-Gleichgewicht; Realoption; Theorie